PEMBENTUKAN KARAKTER MAHASISWA MELALUI PENDIDIKAN ANTI KORUPSI - Yakobus Belo Tobi; Yohanes Oktavianus Dimu; Skolastika Lelu (JAPB: Jurnal Agama, Pendidikan dan Budaya, 2026)
The development of science, technology, and communication can contribute to anti-corruption education in shaping the character of every individual. Corruption is something that can damage the social and economic life that occurs in society. Therefore, anti-corruption education is necessary. Anti-corruption education is a good and strong approach in eradicating corruption. With anti-corruption education, it can build and shape character, strong ethical values, and integrity for everyday life. Anti-corruption education in higher education is very urgent for students as pioneers and leaders in directing the direction of societal development towards a better direction. This study emphasizes the formation of student character through anti-corruption education. The method used in this study is a literature study. This research took place from December 2025 to January 2026. The results of the study indicate that anti-corruption education can shape student character, namely strong ethical awareness, integrity, and an anti-corruption attitude. Through anti-corruption education, student character can be formed and there are ongoing efforts to continue this program to ensure that the younger generation, especially students, can actively participate in preventing corruption now and in the future.